Intersection of Redox Chemistry and Ubiquitylation: Post-Translational Modifications Required for Maintaining Cellular Homeostasis and Neuroprotection - Emma I. Kane; Kelly L. Waters; Donald E. Spratt (Cells, 2021)
Neurodegeneration has been predominantly recognized as neuronal breakdown induced by the accumulation of aggregated and/or misfolded proteins and remains a preliminary factor in age-dependent disease. Recently, critical regulating molecular mechanisms and cellular pathways have been shown to induce neurodegeneration long before aggregate accumulation could occur. Although this opens the possibility of identifying biomarkers for early onset diagnosis, many of these pathways vary in their modes of dysfunction while presenting similar clinical phenotypes. With selectivity remaining difficult, it is promising that these neuroprotective pathways are regulated through the ubiquitin-proteasome system (UPS). This essential post-translational modification (PTM) involves the specific attachment of ubiquitin onto a substrate, specifically marking the ubiquitin-tagged protein for its intracellular fate based upon the site of attachment, the ubiquitin chain type built, and isopeptide linkages between different ubiquitin moieties. This review highlights both the direct and indirect impact ubiquitylation has in oxidative stress response and neuroprotection, and how irregularities in these intricate processes lead towards the onset of neurodegenerative disease (NDD).